Risk factors associated with children learning disorders at school: a socio-medical problem. - Beatriz Sabina Roméu; Zenaida María Saéz; Margarita Roméu Escobar (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
Background: At the polyclinic ´´Area I´´ in Cienfuegos there are no previous studies on learning disorders in children and no epidemiological or exploratory research on personal, family and school issues related to this problem has been conducted. Objective: To determine the differences between children with and without learning disorders in second and third grade in the schools in the area of the "Dr. José Luis Chaviano" polyclinic in Cienfuegos in order to determine the risk factors depending on the child, the school and the family. Method: A non-coupled case-control study was conducted from September 2008 to June 2009. Study group: 42 children presenting learning difficulties as to their teacher´s opinion. Control group: 40 children with normal learning selected by simple random sampling. Interviews were conducted with parents, teachers and children as well as observations of school activities. Standardized questionnaires were applied and the information obtained was processed by using the SPSS statistical program. The chi-square statistic was used and the relative risks were estimated. Results: The identified disorders were associated with mood changes, unattendance to school and poor muscle control for writing, among others mentioned by teachers. The frequent change of teachers was also an associated condition. Among the risk factors related to family issues were: parents´ low educational level, cohabitation, family history of neurotic disorders, inconsistent educational management, family violence, marginalization and understimulation at home. Conclusion: Learning disorders were associated with risk factors depending on the child, school and, in a relevant way, on the family environment factors.